Harnessing marine plant extracts for sustainable agriculture, livestock management, industrial use, and biomedical applications - Yildirim, Metin; Amangeldinova, Madina; Poyraz, Samet; Erşatır, Mehmet; Mussayeva, Aizhan; Kudrina, Nataliya (Frontiers in Plant Science, 2025)
Marine plants are emerging as versatile resources for bioactive compounds with antioxidant, antibacterial, anti-inflammatory, and anticancer properties. Beyond their therapeutic potential, marine extracts offer agronomic and industrial value as biostimulants, natural pigments, biodegradable packaging materials, and green corrosion inhibitors, and serve as reducing agents in the synthesis of biomedical nanoparticles. This review integrates evidence from 256 studies (2011–2025), revealing rapid growth in the field over the past two years. The findings highlight the capacity of marine extracts to enhance crop and livestock productivity, yield stable natural dyes, create smart polysaccharide-based films, and protect metals via phenolic and sulfated polysaccharide fractions. Nanoparticles synthesized from these extracts exhibit improved biological performance. By linking agricultural, industrial, and biomedical perspectives, this work underscores the multifaceted potential of marine plant extracts and outlines future priorities in molecular characterization, strain development, and scalable green processing.